The role of aggression and maladjustment in the teacher-student relationship on burnout in secondary school teachers - Masluk, Barbara; Gascón-Santos, Santiago; Oliván-Blázquez, Bárbara; Bartolomé-Moreno, Cruz; Albesa, Agustín; Alda, Marta; Magallón-Botaya, Rosa (Frontiers in Psychology, 2022)
Introduction Multiple studies have examined the individual and socio-demographic variables that can contribute to the development of burnout in teachers. Although the evidence supports that this syndrome is generated through the interaction between the aspects of the organization and those of the person, little attention has been spent on the impact of the teacher-student relationship adjustment and, especially, on the role of violence exercised by students or their families toward secondary school teachers, who seem to be more vulnerable than teaching professionals in general. Objective To analyze the role of the possible mismatch in the student-teacher relationship, as well as, the physical and verbal violence toward teachers from pupils or their parents, on the professional wear of high school educators. Materials and methods A cross-sectional study was carried out on a teacher sample (n = 677) in Aragón, Spain, through a questionnaire with socio-demographic data; the “Maslach Burnout Inventory” (MBI), “Areas of Worklife Scale,” the “Fears and Rejection in Education Questionnaire” (FREQ), and a list of the possible aggressions received in the development of the teaching activity. Results While 3.8% of teachers have been a victim of physical attacks, 34.9% have suffered verbal abuse at least once. Although physical violence is extremely rare (and low intensity), verbal victimization or threats are associated with burnout in a highly significant manner, which confirms previous findings about school violence and burnout. Also, FEAR and REJECTION dimensions, defined as discomfort, tension, anxiety, and pressure caused by pupils, which contributed considerably on two dimensions of burnout (emotional exhaustion and cynicism). Different covariates such as maladjustment in the teacher-pupil relationship, violence experienced at work, and complaints received explain the 56.4% variance of exhaustion, 48.8% variance in cynicism, and 35.5% for efficacy. Conclusion Very different variables can contribute to the development of burnout syndrome, both personal, and organizational variables. Therefore, when designing prevention programs in each work environment, the possible areas of risk and the interactions between them must be considered.